Ultrasonic Assisted Extraction on Phenolic and Flavonoid Content from Phyllanthus niruri Plant - Nguang, Suok Ling; Yeong, Yi Ling; Pang, Sook Fun; Jolius, Gimbun (Informatics Publishing Limited, 2017)
To find out the effect of ultrasonic assisted extraction with various solvents of phenolic and flavonoid compound extracted from P. niruri. Methods/Statistical Analysis: Phenolic content from P. niruri was analyzed using Singleton’s method while the flavonoid content was analyzed by aluminum chloride colorimetric assay. Findings: The polyphenols extraction was greatly affected by the solvent type and concentration, particle size of the plant powder, solid liquid ratio and frequency. The highest phenolic content and flavonoid content were obtained at the solid ratio of 2g dry weight P. niruri powder at 119.28 mg GAE/g DW and 75.86 mg QE/g DW. Application/Improvements: The phenolic and flavonoid content reached its optimum extraction yield at the particle size of 125 µm, using 40% EtOH as solvent and the extraction yield increased when the ultrasonic frequency is increased to 53 kHz. The extraction method used in this work may serve as a useful guide to obtain optimum polyphenol extraction from P. niruri